Fear Avoidance After Injury and Readiness to Return to Sport in Collegiate Male and Female Gaelic Games Players. (November 2021) - O'Connor, Siobhán; Moran, Kieran; Sheridan, Aishling; Brady, Shaunagh; Bruce, Conor; Beidler, Erica; O'Hagan, Anna Donnla; Whyte, Enda
Background: Injuries are common in collegiate Gaelic games, and negative psychological responses to injury, such as fear avoidance and a lack of psychological readiness to return to sport, can affect players during their rehabilitation and their subsequent return to sport. Thus, identifying these responses in players can allow clinicians to address these issues during rehabilitation. This study aimed to examine fear avoidance and psychological readiness to return to sport in collegiate Gaelic games players. Hypothesis: Collegiate Gaelic games players will experience similar levels of fear avoidance and psychological readiness to return to sport as other adult athletes. Study Design: Cohort study. Level of Evidence: Level 3. Methods: Male (n = 150) and female (n = 76) players from 1 Irish collegiate institution were recruited. Players that were injured over 1 collegiate season completed the Athlete Fear Avoidance Questionnaire (AFAQ) immediately after the injury and the Injury-Psychological Readiness to Return to Sport (I-PRRS) Scale once cleared to return to sport. An injury report form was also completed. The overall AFAQ (sum of 10 items) and I-PRRS (sum of 6 items/10) scores were calculated. Results: Seventy-three injuries (n = 73) occurred, and injured players had a mean overall AFAQ and I-PRRS score of 22.6 ± 5.3 and 46.4 ± 8.8, respectively. Just less than half (47.9%) of players were deemed psychologically unready to return to sport when cleared physically. After severe injuries, significantly higher overall AFAQ scores than mild injuries ( P = 0.01) and lower overall I-PRRS than moderate injuries ( P < 0.0001) was noted. For the overall scores, no gender differences were observed. Conclusion: Fear avoidance and lowered confidence levels before return to sport occurs in collegiate Gaelic games players similar to other student-athletes. Clinical Relevance: Identification of fear avoidance or low readiness to return to sport, particularly after serious injury, is important to implement psychosocial support during their rehabilitation.